Metal-induced neurodegeneration in C. elegans - Aschner, Michael; Chen, Pan; Martinez-Finley, Ebany J.; Bornhorst, Julia; Chakraborty, Sudipta (Frontiers in Aging Neuroscience, 2013)
The model species, Caenorhabditis elegans, has been used as a tool to probe for mechanisms underlying numerous neurodegenerative diseases. This use has been exploited to study neurodegeneration induced by metals. The allure of the nematode comes from the ease of genetic manipulation, the ability to fluorescently label neuronal subtypes, and the relative simplicity of the nervous system. Notably, C. elegans have approximately 60–80% of human genes and contain genes involved in metal homeostasis and transport, allowing for the study of metal-induced degeneration in the nematode. This review discusses methods to assess degeneration as well as outlines techniques for genetic manipulation and presents a comprehensive survey of the existing literature on metal-induced degeneration studies in the worm.